Hierarchically scaffolded CoP/CoP2 nanoparticles: controllable synthesis and their application as a well-matched bifunctional electrocatalyst for overall water splitting. Issue 17 (20th April 2017) - Li, Wan; Zhang, Shilin; Fan, Qining; Zhang, Fazhi; Xu, Sailong
Abstract : Well-dispersed CoP/CoP2 nanoparticles were used as a bifunctional electrocatalyst, and in situ XRD reveals that a topotactic transformation and enhanced electrocatalytic activities were achieved. Abstract : Transition metal phosphide (TMP) nanostructures have stimulated increasing interest for use in water splitting owing to their abundant natural sources and high activity for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Typically, the preparation of hierarchical TMPs involves the utilization of expensive or dangerous phosphorus sources, and, in particular, the understanding of topotactic transformations of the precursors to crystalline phases—which could be utilized to enhance electrocatalytic performance—remains very limited. We, herein, report a controllable preparation of CoP/CoP2 nanoparticles well dispersed in flower-like Al2 O3 scaffolds (f-CoP/CoP2 /Al2 O3 ) as a bifunctional electrocatalyst for the HER and OER via the phosphorization of a flower-like CoAl layered double hydroxide precursor. Characterization by in situ X-ray diffraction (XRD) monitored the topotactic transformation underlying the controllable formation of CoP/CoP2 via tuning the phosphorization time. Electrocatalytic tests showed that an f-CoP/CoP2 /Al2 O3 electrode exhibited a lower onset potential and higher electrocatalytic activity for the HER and OER in the same alkaline electrolyte than electrodes of flower-like and powdered CoP/Al2 O3 . The enhanced electrochemical performance was experimentally supported by measuring the electrochemically active surface area. The f-CoP/CoP2 /Al2 O3 composite further generated a current density of 10 mA cm −2 at 1.65 V when used as a bifunctional catalyst for overall water splitting. Our results demonstrate that the preparation route based on the LDH precursor may provide an alternative for investigating diverse TMPs as bifunctional electrocatalysts for water splitting.